A MULTIDISCIPLINARY APPROACH TO TREATMENT OF HIGH FLOW HEAD AND NECK ARTERIOVENOUS MALFORMATIONS: SINGLE CENTRE EXPERIENCE IN 7 COMPLEX CASES: Multidisciplinary Approach in Head and Neck AVMs - Ahmad, Saima; Akhlaque, Roomana; Uddin, Moeez; Rashid, Umair; Churojana, Anchalee; Khan, Muhammad Aslam (Journal Of Cardiovascular, Neurovascular & Stroke, 2022)
Introduction: The objective of this work is to determine the role of a multidisciplinary approach in treating the complex high flow head and neck arteriovenous malformations (AVMs), involving radiologists and plastic surgeons for the best possible outcomes. Methods: Between 2018 and 2020, the investigators conducted a retrospective analysis on seven patients with high-flow head and neck AVMs who received treatment at a tertiary care facility. Age at first diagnosis, presenting features, prior therapies, endovascular treatment, surgical treatment, and therapeutic outcomes were all recorded. A comparison of pre-and post-procedure pictures was made to assess the clinical outcomes for all patients. Results: Seven patients with complex high flow head and neck AVMs were jointly managed by performing plastic surgery and interventional radiology. There were male and female, with an average age of 24 years. Each patient underwent embolization followed by surgical resection within a 24-hour window of up to 72 hours. In six out of seven patients, the lesion was removed therapeutically, whereas the seventh required palliative resection. Only one patient, there was a minor wound healing difficulty able to be treated with dressings. Conclusion: The results revealed that embolization alone is not effective to reduce the adverse effects. Incomplete removal of AVM showed the same effect as incomplete removal of a tumour. It may not improve symptoms and may worsen the recurrence, thus multi-modality approach is beneficial. A multidisciplinary approach, aided by the interventional radiologist and enable plastic surgeons to remove the high-flow AVMs effectively.